MANAGEMENT OF ABANDONED LAND IN THE PERSPECTIVE OF ISLAMIC LAW AND NATIONAL LAW OF LAND - Ridwan . (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2016)
Abstract:This article is aimed at showing that land has not only economic values, but also social values. Abandoning land indicates ignorance to both values and is against legal norms, both religious and state norms in Indonesia. The consequence of abandoning land by the owner, either in Islamic or national law perspective, will result in the banning of the rights of its possession by the state who has the authority to manage the use of land for social welfare. This article proves that both Islamic and national laws have a similarity in the basic law aspect, that land should have social and economic functions. The state has the juridical authority to ensure that land is used for social welfare, including assuring that there is no land abandoned by its owner. Abstrak:Artikel ini menunjukkan bahwa tanah di samping bernilai ekonomis, juga memiliki nilai sosial. Penelantaran tanah menunjukkan, selain adanya pengabaian terhadap kedua nilai tersebut, juga bertentangan dengan norma hukum, baik hukum Islam maupun hukum positif Indonesia. Konsekuensi penelantaran tanah yang dilakukan oleh pemilik tanah baik menurut hukum Islam maupun hukum nasional mengakibatkan pemerintah sebagai pemilik otoritas memiliki kewenangan untuk menarik kembali dan menjadikan tanah tersebut untuk kemaslahatan sosial. Artikel ini membuktikan bahwa antara hukum Islam dan hukum nasional memiliki kesamaan pada aspek hukum asas bahwa tanah harus memiliki fungsi sosial. Negara memiliki otoritas untuk memastikan bahwa tanah harus bias menjalankan fungsi kemaslahatan sosial termasuk menjamin tidak adanya tanah yang ditelantarkan oleh pemiliknya.